2019
DOI: 10.5194/isprs-archives-xlii-5-w2-1-2019
|View full text |Cite
|
Sign up to set email alerts
|

Scan-to-Bim Methodology Adapted for Different Application

Abstract: <p><strong>Abstract.</strong> In this paper we proposed a methodology that describes the major steps of a scan-to-BIM process. The methodology includes six steps: (1) classification of considered elements, (2) definition of required level of detail (GI), (3) scan data acquisition, (4) point cloud registration and segmentation, (5) as-built BIM creation and (6) analysis. The examples of the application of the proposed methodology are demonstrated by creation of as-built BIM models for existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 20 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Existing object modeled in Autodesk Revit software from laser scanning and point cloud processed in Autodesk Recap software. In this case, the so-called Scan-to-BIM technology [10] is used. The resulting information model is semantically saturated both with the properties of materials and due to the binding of documentation to the elements of the object, groups of the object and the object as a whole.…”
Section: Methodsmentioning
confidence: 99%
“…Existing object modeled in Autodesk Revit software from laser scanning and point cloud processed in Autodesk Recap software. In this case, the so-called Scan-to-BIM technology [10] is used. The resulting information model is semantically saturated both with the properties of materials and due to the binding of documentation to the elements of the object, groups of the object and the object as a whole.…”
Section: Methodsmentioning
confidence: 99%
“…As BIM models require accurate spatial information of building parameters, laser scanning is commonly adopted to collect this data (Badenko et al, 2019). This approach that exploits laser scanning is referred to as a scan-to-BIM process (Bosché et al, 2015).…”
Section: Laser Scanningmentioning
confidence: 99%
“…This approach that exploits laser scanning is referred to as a scan-to-BIM process (Bosché et al, 2015). Appropriate 3D data for creating as-built BIM models can be produced by all types of laser scanning devises and techniques, including terrestrial, mobile and airborne methods (Badenko et al, 2019).…”
Section: Laser Scanningmentioning
confidence: 99%
“…Experience in the development of methods and algorithms for processing hybrid data of laser scanning and photography has shown that the resulting point clouds without noise and clutter are of great practical importance [50][51][52][53]. The main di culties when working with such clouds are associated with the fact that the initial data stream is very heterogeneous, in three-dimensional space only the surfaces of objects are obtained and point clouds are huge.…”
Section: State Of the Artmentioning
confidence: 99%